Ginsenoside Rg1 Acts as a Selective Glucocorticoid Receptor Agonist with Anti-Inflammatory Action without Affecting Tissue Regeneration in Zebrafish Larvae - He, Min (Cells, 2020)
Glucocorticoids are effective anti-inflammatory drugs, but their clinical use is complicated due to the wide range of side effects they induce. Patients requiring glucocorticoid therapy would benefit from more selective glucocorticoid receptor (GR) agonists, capable of attenuating the immune response without causing these side effects. Ginsenosides, such as the compound Rg1, are natural plant compounds with structural similarity to classical glucocorticoids and well-documented anti-inflammatory effects. Here, we have investigated the activity of the ginsenoside Rg1 using a zebrafish larval model, in which amputation of the tail fin allows us to assess drug effects on inflammation, while the ability to regenerate the wounded tissue serves as a readout for side effects. We found that Rg1 attenuates neutrophilic inflammation at the amputation site, similarly to a classical glucocorticoid, beclomethasone. Mutation of the Gr abolishes this anti-inflammatory effect of Rg1. Rg1 and beclomethasone differentially modulate gene expression, suggesting that Rg1 induces transrepression, but not transactivation, activity of Gr. Interestingly, we found no effect of Rg1 on tissue regeneration, whereas beclomethasone inhibits tissue regeneration entirely. We conclude that Rg1 is a promising candidate for development as a selective glucocorticoid drug, and that zebrafish larvae provide a useful model system for screening of such GR agonists.